Elements of the Orthodox communication system - Petrushkevych, Mariya S. (Ukrai͏̈ns'ke relihijeznavstvo, 2006)
For many centuries, religious beliefs, ecclesiastical institutes, and religious practices have dominated and radically influenced secular manifestations of social consciousness, social organization, and culture. Religion through the development of certain doctrines and religious practices and the church, not only as a sacred concept, but also as a social institution uniting the followers of a particular religion, are very important areas of our reality. Therefore, the impact of religion on the mentality is deep and diverse.